An Interactive 3D Modeling Tool for Creating and Managing Soft Body Animations - Strandell, Razmus (My University, 2020)
Computer animations are commonly deployed in various fields today, such as the movie industry, video game industry and in architecture. This has led to an increase in the demand for 3D modeling tools that can be used to create these animations. The goal of this project is thus to explore what considerations exist when developing interactive 3D modeling software. This was explored by conducting researching in the area, including existing 3D modeling tools and other related work, and by designing and implementing an interactive 3D modeling tool as per the research through design practice. This tool was built around generating generic soft body animations. The tool was first designed using an iterative design process, including methods ranging from ideation techniques to evaluation methods. The software part was then developed using a mix of popular agile software development methods. The code was developed with focus on ensuring optimal performance, promoting software modularity and minimizing external dependencies. The end result is a high fidelity software prototype that can be used to create animations of varying complexity. The development of the tool, alongside the conducted research, resulted in a set of guidelines to consider when developing similar tools. These guidelines can be summarized as the following: what external libraries to use, what work process to use, what features should be available, how to design for different user groups and how to make the code modular. Despite the guidelines resulting from the work of this specific tool, they are considered to be applicable to the development of 3D modeling software that handles any kind of soft body animations.
Keywords: 3D modeling; computer animation; soft body animation; user experience